ANALISIS HUBUNGAN KEBISINGAN MESIN DENGAN STRES KERJA (Studi Kasus : Mesin TWO FOR ONE TWISTER (TFO) PT. XYZ) - Budiawan, Wiwik; Ulfa, Ema Amalia; Andarani, Pertiwi (Universitas Diponegoro, 2016)
The Two for One Twister (TFO) machine emits very disturbing noise and the noise exposes the workers while performing their tasks. The noise also lead to works stress. So, it is necessary to determine the relationship between the noise and work stress of TFO machine operators. This study was conducted by measuring the noise of TFO engine with Enviro-meter and then correlating the noise and work stress with SPSS 16 software. Spearman correlation test results showed that a strong correlation between noise with work stress (p value = 0.042). In order to reduce the noise level that will decrease stress for workers, Fault Tree Analysis was conducted to determine the source of the noise. Based on the qualitative analysis of FTA, the causes of the noise were as follows: the lubricating oil was not applied, seal of oil valve leaked, bearing was not replaced (2 years economic life), the traveler was not replaced (10 days economic life), and the Doubling machine was troubled. Based on the quantitative analysis of the probability of job stress of TFO machine operator due to noise TFO machines from a known probability of 0.041, hence, the system was feasible for use.